Ensino de filosofia na socioeducação: uma perspectiva pluriversal e antirracista - Silva, Paulo Renato Oliveira (2021)
This research dissertates on the Teaching of Philosophy for classes of first grade of high school in the correctional-measures educational centers IASES in Cariacica - ES, emerging from the need for an anti-racist proposal in education. This need is caused by the racial cutout phenomenon of young inmates, the majority of the population being black. Aiming to break the racist structures of western societies, we propose a Teaching of Philosophies, promoting for these young people an approach beyond western canons. In the development of this proposal, we´ve faced several challenges, from the difficulty of schoolbooks that contemplate Law 10.639/03 to an effective method for the parameters of socio-education. With this panorama in our research reality, we will deal with aspects that prove the structural racism of our public institutions. Overcoming some of these challenges, this research has as a practice teaching Ubuntu ethics proposed by the South African philosopher Mogobe Ramose, resorting to the ancestral tradition of philosophizing and teaching through orality. This tradition has become extremely important, once socio-measures students do not have access to philosophical texts outside the classroom environment for safety reasons. This approach was satisfactory in the proposal of this research. Thus, breaking the racist structures of our culture, this work rises the opportunity of thinking about a socioeducation free from the colonial bonds of our people, practicing a Teaching of Philosophy that can be evidential for the students.